DIAGNOSTIC CRITERIA FOR COVID - 19 COMBINED WITH PNEUMONIA - Turdiev Khurshid Kobilovich (Journal Park Publishing, 2022)
The COVID-19 virus infection, which has been classified as a pandemic by WHO, is caused by a representative of the group of coronaviruses, which, in turn, belong to the family of seasonal SARS. The SARS-CoV-2 disease, dubbed COVID-19, was officially declared a pandemic by the World Health Organization on March 11, 2020. SARS-CoV-2 contains a single-stranded positive-sense RNA genome surrounded by an extracellular membrane containing a series of crown-like spike glycoproteins.